ANALISIS STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN JUMLAH NASABAH TABUNGAN SUKARELA (SIRELA) DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAITUL MAAL WA TAMWIL (KSPPS-BMT) MAKMUR MANDIRI SUKOHARJO TAHUN (2019-2021) - Hasan Baihaqi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
There are now many Islamic Financial Institutions in Indonesia that have sprung up by offering a variety of superior products. Sharia Financial Institutions are also in great demand by the public because of their product claims and services based on Sharia. One of the institutions that was established was KSPPS-BMT Makmur Mandiri Sukoharjo, namely a cooperative that runs its financial operations based on Sharia and based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 16 /Per/M.KUKM/IX/2015 concerning Implementation of Business Activities. Savings and Loans and Sharia Financing by Cooperatives. The purpose of this study was to determine the marketing management system implemented by KSPPS-BMT Makmur Mandiri Sukoharjo to gather as many members as possible. The research method used is descriptive qualitative. Sources of data in the form of interviews, observations, and documentation. The results of the study stated that KSPPS-BMT Makmur Mandiri Sukoharjo had implemented 6Ps in marketing strategy. Namely Product, SIRELA as a superior product. Place, the head office is located near the market. Price, the price of a minimal deposit and a light minimum of saving. Promotion, through door to door strategies, brochures, product superiority offers, and promotions by utilizing social media. People, employees or cooperative employees who are ready to serve and provide information to members. Process, applying the pick-up method, namely KSPPS-BMT Makmur Mandiri Sukoharjo employees come to visit consumers or partners who want to save, making it easier for members who do not have time to come to the office directly. Currently KSPPS-BMT Makmur Mandiri Sukoharjo has collected up to 6,659 consumers in the 2019-2021 period.